Pengaruh Sistem Pengendalian Manajemen terhadap Kinerja Manajerial pada Bank Syariah Indonesia, Kc Aceh Diponegoro - Fachruddin, Rudy; Labok, Cresensia Sinai; Saputra, Mulia (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2024)
This study aims to determine the influence of the management control system and on managerial performance at Bank Syariah Indonesia, KC Aceh Diponegoro. This research is a quantitative research method using primary data sources in the form of questionnaires. The population in this study was all managers and employees of Bank Syariah Indonesia KC Aceh Diponegoro with 35 respondents. The analysis method used in this study is a simple linear regression analysis with SPSS 26 tools. The results showed that the management control system variable has a significance value of 0.000 > 0.05, so that the management control system has a significant effect on managerial performance at Bank Syariah Indonesia, KC Aceh Diponegoro.